Numerical simulation on continuous penetrating/blasting behavior of multi-projectiles against concrete target. (March 2020) - Wang, S P; Tan, J Z; Su, C H; Zheng, Y F
Abstract: Deep digger weapon system uses continuous kinetic energy and chemical energy of the penetrating/blasting projectiles to dig the concrete target. In the present paper, numerical simulations are conducted to study the continuous penetrating/blasting effects of multi-projectiles against concrete target. The simulation results show the KE penetration produces the crushing and rupturing zone, providing conditions for subsequent damage due to explosions. Then, the explosion further increases the diameters of the crushing and rupture area, and the cracks propagate inside the concrete target. The second penetration and blast further increase the depth and the damage area, achieving deep digger behavior to the concrete target. However, the throwing effect of secondary penetration/blast is slightly weaker than that of first one. Moreover, the simulation also shows the continuous penetrating/blasting behavior is influenced markedly by impact velocity.